Integration of Digital Technology in Thematic Learning in the Independent Curriculum in Elementary Schools - Muhammad Reihan Saputra; Indy Kurniawan; Muhamad Ilham Kurniawan Fazza Abdulah; Harisa Saputra; Agus Dwi Prasojo (Civiliza Publishing, Indonesia., 2026)
In the 21st century, the use of technology in the learning process is no longer an option, but has become an obligation to improve the quality of education and form a generation that is able to adapt to the challenges of the global world. This study aims to analyze the integration of digital technology into thematic learning within the Merdeka Curriculum in elementary schools. The advancement of digital technology in the field of education demands learning innovations capable of improving the quality of the teaching and learning process. Digital technology serves not only as a tool but also as an integral part of creating interactive, adaptive, and student-centered learning. This aligns with the concept outlined in previous research, which emphasizes that the use of digital media can enhance 21st-century competencies and support the implementation of the Merdeka Curriculum. This study employs a qualitative approach using a literature review method. The findings indicate that the integration of digital technology into thematic learning is achieved through the utilization of various media, such as educational videos, digital platforms, and technology-based instructional materials. The use of these technologies is able to increase student engagement, motivation, and understanding of the learning material. This is also reinforced by findings in previous research, specifically the Digital Technology-Based Learning Models, which state that technology can create more meaningful and personalized learning experiences for students.